Chiquinha Gonzaga: a woman in song - Mello, Denise (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
At the end of the 19th century, the woman was subject to her father and later to her husband. Her main occupation was housework – the care of her family. However, some women broke with the recurring male chauvinist and began to professionalize themselves. Few stood out and had their names valued in our musical history as Chiquinha Gonzaga (1847-1935). Chiquinha is one of the female songwriters mentioned in the research carried out by Denise Mello in the book The Woman in Song: the feminine composition in the Radio Era. Although Chiquinha had already composed before this period, she is the greatest representative of female composition in Brazil thanks to an extensive and quality work, in addition to a vanguard behavior at the time. She also became a great instrumentalist and the first woman to conduct an orchestra. This article contains biographical information and song parts written by the female composers with links to the song audios. Denise writes about female composition in Brazil and explores why female songwriters were erased in Brazilian musical history.